Optimization of dose and image quality in full field and computed radiography systems for common digital radiographic examinations - Moey, Soo Foon; Ahmad Shazli, Zubir (Iranian Association of Medical Physicists (IAMP), 2018)
Introduction: Optimization facilitates image quality and radiation dose by minimizing stochastic and deterministic effects. This study was to obtain images of acceptable quality with no harmful effects for common radiographic examinations in digital imaging. Materials and Methods: This study was conducted in three phases. The pre-optimization phase involved 90 physically able patients weighing 60-80 kg and aged 20-60 years. The estimation of dose and image quality was performed on four common digital radiographic examinations. The entrance surface dose (ESD) and effective dose (ED) were measured using a DAP meter (Kerma X_plus) and CALDose_X 5.0 Monte Carlo software, respectively. The second phase, an experimental study utilized an anthropomorphic phantom (PBU-50) and TOR CDR Leeds test object for comparison of image quality. In the optimization phase, the imaging parameters with acceptable image quality and lowest ESD from the experimental study were adjusted for patient’s body thickness. Image quality was evaluated by two radiologists using the modified evaluation criteria score lists. Results: A significant difference was observed between the pre- and post-optimization phases for all examinations for image quality. However, ESD was significantly different between the two phases for PA chest and AP abdomen. The ESDs for three of the examinations were lower than those reported in all published studies. The ESD and ED obtained for all examinations were lower than recommended by radiation regulatory bodies. Conclusion: The optimization of image quality and dose was achieved by utilizing an appropriate tube potential, calibrated automatic exposure control, and additional filtration of 0.2 mm copper.